The JENAKA Game: Stimulating Gross and Fine Motor Development in Early Childhood - Kartika, Wilda Isna; Maghfirah, Febry; Azzahra, Vira; Hasnur, Reyzia Anggriani; Pertiwi, Adharina Dian (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2025)
Problems of motor development delays in early childhood remain prevalent, often linked to decreasing levels of physical activity and the rising use of digital gadgets. This study aimed to investigate the effect of the interactive game JENAKA (Jelajah Fauna Kalimantan/Exploring Kalimantan’s Fauna) in stimulating motor development in children aged 5–6 years. A quantitative approach was employed using a pre-experimental design with a One Group Pretest–Posttest structure. The participants consisted of 18 children selected through saturated sampling, and the intervention was conducted over ten sessions between July and October 2024. Data were collected through structured observation using a motor skills instrument adapted from established measures, comprising 17 items across two domains: gross motor skills and fine motor skills. Expert validation confirmed content appropriateness, and the instrument demonstrated acceptable reliability. Data analysis involved tests of normality and homogeneity, followed by paired samples t-test using SPSS. Results revealed a significant improvement in motor skills after the intervention, with a significance value of .001, well below the .05 threshold. These findings indicate that JENAKA effectively enhanced both gross and fine motor skills, demonstrating its potential as an innovative learning medium in early childhood education. The novelty of this study lies in integrating local cultural and ecological elements, particularly Kalimantan’s fauna, into interactive play, thereby fostering not only physical development but also environmental awareness. The research highlights the importance of culturally grounded, play-based interventions and provides practical implications for curriculum design, suggesting that interactive cultural games can serve as engaging and holistic tools for stimulating early childhood development.